Let’s draw molecules: Students’ sequential drawing processes of resonance structures in organic chemistry - Braun, Irina; Langner, Axel; Graulich, Nicole (Frontiers in Education, 2022)
Drawing is a fundamental skill in STEM disciplines to express one’s reasoning and externalize mental models in problem-solving. Although research has highlighted the effectiveness of drawing as a learning strategy and the importance of drawing accuracy for learning success, little is known about learners’ actual drawing process. However, especially in organic chemistry, the investigation of drawing processes is of great importance as generating different representations, such as structural formulas, is inherent to problem-solving in this visual-laden discipline. Resonance structures, for example, are often used to estimate reactive sites in a molecule and thus propose reaction pathways. However, this type of representation places a high cognitive demand on learners, which, besides conceptual difficulties, leads to drawing difficulties. To support learners in drawing and using resonance structures in problem-solving, it is necessary to characterize how they generate their drawings. To this end, a qualitative, exploratory study has been conducted to investigate undergraduate students’ (N = 20) drawing processes of resonance structures while solving an organic case comparison task. Using eye tracking, the characteristics regarding the construction of productive and unproductive drawings became visible. Results indicate that unproductive drawings often stem from integrating and connecting unrelated information during the drawing process. Further, the results show that the productivity of a drawing depends on learners’ flexibility in information selection. Implications for supporting learners’ drawing process are discussed.